2019
DOI: 10.1159/000500020
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Preoperative Mechanical Bowel Preparation in Patients with Colon Cancer who Undergo Elective Surgery: A Prospective Randomized Trial Using Oral Antibiotics

Abstract: Background: To prevent surgical site infection (SSI) in colorectal surgery, the combination of mechanical bowel preparation (MBP), oral antibiotic bowel preparation (OABP), and the intravenous antibiotics have been proposed as standard treatment. We conducted an RCT comparing the incidence of SSI between MBP + OABP and OABP alone after receiving a single dose of intravenous antibiotics. Methods: The study group comprised 254 patients who underwent elective surgery for colon cancer. Patients were randomly assig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 34 publications
(43 reference statements)
1
17
0
Order By: Relevance
“…In general, different antibiotic regimens are used in accordance with local availability of drugs and possible side effects. Most of the studies report the use of either an aminoglycoside (i.e., neomycine [16][17][18], kanamycine [19], streptomycin [20], gentamicine [21]) or a fluoroquinolone (levofloxacine [1] or ciprofloxacine [15]) plus metronidazole. Additionally, in all present studies, single-shot antibiotics were used preoperatively, mostly consisting of an IV application of a secondgeneration cephalosporine plus metronidazole intravenously.…”
Section: Introductionmentioning
confidence: 99%
“…In general, different antibiotic regimens are used in accordance with local availability of drugs and possible side effects. Most of the studies report the use of either an aminoglycoside (i.e., neomycine [16][17][18], kanamycine [19], streptomycin [20], gentamicine [21]) or a fluoroquinolone (levofloxacine [1] or ciprofloxacine [15]) plus metronidazole. Additionally, in all present studies, single-shot antibiotics were used preoperatively, mostly consisting of an IV application of a secondgeneration cephalosporine plus metronidazole intravenously.…”
Section: Introductionmentioning
confidence: 99%
“…23 Similar decrease of infectious complications was reported by several other studies. 11,24,25 An added advantage of MBP and OABx was the remarkable cost saving in association with diminished incidence of surgical site infection. 26 We also found that bowel preparation in MBP and OABx was associated with reduction of postoperative complications, including mortality, and concomitant shortening of the length of hospital stay.…”
Section: Discussionmentioning
confidence: 99%
“…10 In sharp contrast, other studies have demonstrated clear advantage of MBP in reducing both AL and SSI. 11 It appears that a key factor explaining the divergent results from the currently available literature is the lack of consideration of the influence of oral antibiotics (OABx) on adequacy of preoperative bowel preparation. 12 In this context, MBP is supposed to enhance the uptake of OABx by colonic mucosa.…”
mentioning
confidence: 99%
“…The need for an RCT to determine this has long been discussed , because data on OAB alone are contradictory. Different reports show that the use of OAB alone is worse than , equivalent to or better than the MOAB combination in reduction of SSI. The problems are a lack of RCTs that focus on OAB alone in the absence of MBP, small numbers in the OAB alone groups and selection bias in the cohort studies.…”
Section: Arguments Against the Use Of Moabmentioning
confidence: 98%
“…The need for an RCT to determine this has long been discussed [17, 84,85], because data on OAB alone are contradictory. Different reports show that the use of OAB alone is worse than [24,25,27,[29][30][31]43,86], equivalent to [22,26,28,42,87] The problems are a lack of RCTs that focus on OAB alone in the absence of MBP, small numbers in the OAB alone groups and selection bias in the cohort studies. In the largest and most recent meta-analysis [42], SSI rates were compared between patients having MOAB and OAB alone.…”
Section: Arguments Against the Use Of Moabmentioning
confidence: 99%